Studi Fisikokimia Betasianin Dalam Kulit Buah Naga dan Aplikasinya Sebagai Pewarna Merah Alami Sediaan Farmasi: Physicochemical Study of Betacyanin from Dragon Fruit Rind and Its Application as Natural Dye for Pharmaceutical Dosage Form - Asra, Ridho; Yetti, Rina Desni; Rusdi, Rusdi; Audina, Selly; Nessa, Nessa (Universitas Tadulako, 2019)
The rind of dragon fruit (Hylocereus lemairel (Hook.) Britton & Rose) is a waste material that has not been optimally utilized. The rind contains betacyanin pigment that has many benefits in pharmaceutical products. The study aimed to characterize the physicochemical properties, to evaluate the stability and to apply betacyanin in dragon fruit rind as a natural dye. The extraction process was done by using water as solvent which was sonicated at 50 kHz for 30 minutes at 25 Â°C. Extract was freeze dried for 48 hours. The dried extract was purified by using preparative TLC and physicochemically analyzed by using UV-Vis and FTIR spectrophotometer. The stability of betacyanin extract against pH and temperature was examined and applied as a dye in tablet imprinting. The result of this study indicated that betacyanin was found at Rf value of 0.6 same as the betacyanin standard. The maximum wavelength of betacyanin was obtained at 534 nm and the IR spectra showed similarity with betacyanin standard with the same functional groups between 4000-600 cm-1 although there was a slight shift in the wavenumber but it still in the range. The stability study were stable at temperature below 40 Â°C and at range pH 4-6. Betacyanin applications as natural dye of tablet have been successfully carried out with good color stability during 3 months of storage at room temperature.